Kon Satoshi and Japan’s Monsters in the City - Perkins, Chris (Nordlit, 2019)
This article offers an analysis of Kon Satoshi’s use of monsters in his 2004 animated television series Paranoia Agent (Mōsō Dairinin). Focussing on the bat-wielding figure of Shōnen Batto and a cuddly pink doll called Maromi, it is shown how Kon Satoshi uses these figures to critique a range of fatalistic discourses on Japan’s decline that have emerged since the bursting of Japan’s economic bubble in the early 1990s. I argue Kon repackages the ‘vague sense of anxiety’ prevalent in post-bubble Japan as monster in order to access the psychic realities of Japan, and as a tool for developing a critique of Japan’s fear of and fascination with social monsters. Through analysis of key scenes, the article shows how Kon develops a rich dialectical understanding of Japan’s on-going search for monsters, while also forwarding his own humanist view of social responsibility as method of navigating the ever-changing social environment of late-modern Japan.